Pengembangan Medical Tourism dengan Teknologi preventive: Medical Wellness Riskha Dora Candra Dewi - Riskha Dora Candra Dewi (Consilium Sanitatis: Journal of Health Science and Policy, 2023)
Objective: This study aims to examine the Development of Medical Tourism with Preventive Technology: Medical Wellness. Methods: This research was studied using the literature study method, sourced from national and international journals. Journal sources used include Pubmed, Google Scholar, Elsevier, and ResearchGate. Results: The study results show that telemedicine and telehealth (or e-health systems) covering all health service providers that use information and communication technology for diagnosis, treatment and prevention of health services can become a preventive technology in the practice of medical tourism and medical wellness in Indonesia. This is because information and communication technology development can be an essential factor in realizing the successful development of medical tourism in Indonesia. Conclusion: The reputation of Bali's tourism infrastructure in Indonesia and the ASEAN region is relatively well established. Growth in health and wellness travel due to improved infrastructure, tourist demand, the hospitality sector and a well-regulated business environment. However, such a comparative advantage does not guarantee that Bali will be able to compete in a world where tourist preferences are the driving force of competition.